Studi Analisa Rele Jarak Pada Jaringan Transmisi 150 Kv Gardu Induk Pedan - Gardu Induk Jajar - Ariyanto, Rika; Hasan, Umar, S.T., M.T (2017)
Protection system is a part of an electric power system that is very important to improve the continuity of service to consumers, where components and tools that are part of the system must have the sensitivity, selectivity, speed, security and maximum reliability in operational. Relay distances classified in one part of the protection system is used as a safety on the transmission line because of his ability to eliminate distractions quickly, setting relatively easy and has a coverage area of broad protection, and therefore things related about performance issues of a tool such safety relays need to be considered on the network. Based on the working principle ofrelay distance and setting relay that has been applied in the field, the methods used in the analysis of relay distance along the transmission line of 150 KV substation Pedan - Substation Jajar is to find the data source parameters, parameter transformer, and cable conductor. Data impedance setting relay which has been adopted by the PT. PLN (Persero) compared again with the analysis of theoretical calculations performed as an evaluation of the quality of security in the transmission line. Results comparison impedance setting of PT PLN (Persero) with the theoretical calculation analysis there is a difference for each zone of protection which is divided into three parts as follows: 1 = 0.2 Ω zone, zone 2 = 0.2 Ω, zone 3 = 0.28 Ω. The difference between the calculations based on the analysis of differences in the possible by several factors that are capable of causing an impedance changes because basically transmission parameter channel that is always changing the existing problems.